Penerapan Model Blended Learning Menggunakan PhET Dalam Meningkatkan Motivasi Dan Hasil Belajar Fisika - Atik Indri Astuti (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
This study aims to determine the increase in motivation and learning outcomes of students in class XII MIPA 4 SMA Negeri 1 Jawilan for the academic year 2022/2023. The blended learning model uses PhET in Physics as a learning model for static electricity. This research is a classroom action research which was carried out for two cycles. Each cycle consists of stages of planning, action, observation, and reflection. The learning strategy used is the application of the blended learning model using PhET. The results of this study indicate that the blended learning model using PhET can increase motivation and learning outcomes in Physics subjects as evidenced by the test results at the end of the first cycle there is 1 student with a mastery percentage of 27.77% and an increase in the percentage of completeness in the second cycle of 94.22% of 36| students This shows that the target percentage of students' mastery has increased significantly.